Secondary Science Teachers Perception on STEM Learning for Sustainable Development - Abdul Aziz Rahman; Ida Kaniawati; Riandi Riandi; Sumar Hendayana (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of study is to analysis secondary science teachers’ perception on STEM learning for sustainable development (STEM for SD). Data collected by online questionnaires instrument with 96 teachers as respondent. The data analyzed descriptively. Research finding is 36,5% knowing the ESD and only 26% (low) knowing without misconception and accurate explanation about it. Only 19 % (low) science teacher ever to implement ESD in their schools’ program. School program on ESD such us renewable energy, waste management, environmental education, nature laboratory, and etc. The conclusion is science teacher perceptions increasing public understanding and awareness on ESD are still low. Because that teachers training program on ESD need to be implemented.